INCREASING ECONOMIC GROWTH THROUGH GREEN AGRICULTURE IN INDONESIA - Wisnujati, Nugrahini Susantinah; Siswati, Endang; Nainggolan, Ananda Fitria; Solehodin (PT. Sangadji Media Publishing, 2024)
Economic growth is the primary condition of economic development. With growth, investment, increased employment opportunities, and equity are possible. Many factors are interconnected and affect economic growth. However, rapid economic growth in Indonesia has also caused environmental damage. This study aims to study the factors that affect the level of environmental pollution in Indonesia and the factors that have the most significant influence. This study used a multiple regression model. The results showed that the GDP variable (X1) and rice production variable (X2) had a significant simultaneous relationship with environmental pollution (Y), with an F value of 3.694 and a significance level of 0.032. The t-test results show that rice production (X2) has a significance value of 0.039, or below 0.05. indicates that rice production in Indonesia contributes significantly.